Management of Cervico-vaginal and Rectal Prolapse in Goat during Advanced Pregnancy - Bhat, Ghulam Rasool; Nisa, Masrat un; Yousuf, Nahida; Singh, Pawan preet; Parrah, Jalaluddin (The Indian Journal of Animal Reproduction, 2022)
An apparently healthy doe with a history of bright red protruding cervico-vaginal and rectal mass through the vulva and anus, respectively, and continuous straining efforts was successfully managed till kidding with Buhner sutures using silk under epidural anesthesia.
Keywords: Cervico-vaginal prolapse; Rectal prolapse; Doe; Buhner’s suture